Market Externalities of Tax Evasion - Irene Di Marzio; Sauro Mocetti; Enrico Rubolino; Enrico Rubolino (CESifo GmbH, 2025)
This paper presents evidence of market externalities of tax evasion: firms' tax non-compliance distorts the outcomes of their competitors. Using novel administrative data on the universe of Italian firms, we compute a tax evasion proxy as the fraction of individual firms that manipulate their revenue to meet eligibility criteria for preferential tax regimes. Our empirical approach uses policy-induced changes in tax notches' size to predict the fraction of non-compliant firms in each market. We find that non-compliant firms lead to significant revenue and productivity losses for their competitors, who then pass on some of this burden to their workers. This unfair competition harms aggregate productivity, partly due to a worsening of allocative efficiency. Our findings show that cracking down on tax evasion not only increases tax revenue and promotes tax fairness, but can also enhance market efficiency by leveling the playing field.
Keywords: H26; H25; D22; D43; 330; tax evasion; market competition; preferential tax regimes